Procedural Efficiency vs Legal Certainty in Islamic Finance Disputes: A Maṣlaḥah and Saddu Al-Żarī’ah Analysis - Wijayanti, Dwi Marlina; Luthfi, A Hashfi (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2025)
Abstract: The resolution of Islamic economic disputes involving land collateral without mortgage titles reveals a persistent tension between procedural efficiency and the certainty of creditor protection. This study examines patterns in Indonesian Religious Court rulings through a case study of Sumenep No. 1/Pdt.G.S/2020/PA.Smp, combining a normative analysis of statutory and judicial regulations with an empirical reading of the court decision. The findings indicate a strong pro-efficiency orientation: simplified claims are accepted, contract validity is upheld based on Article 1320 of the Civil Code, and access to justice for small-value disputes is expanded. However, this also weakens the creditor’s legal position, as non-mortgage collateral does not provide executorial title or preferential rights. The mapping confirms a regulatory gap concerning non-mortgage collateral in Islamic economic transactions and inconsistent judicial reasoning across cases. The maṣlaḥah mursalah framework evaluates the benefits of procedural acceleration as legitimate only when it does not erode execution certainty, while saddu al-żarī‘ah emphasizes closing potential harm channels, such as opportunistic debtor behavior and increased financing costs. Policy recommendations include harmonizing the Mortgage Law, the Indonesian Religious Courts Law, and simplified claim procedures; drafting national technical guidelines for judges on verifying non-mortgage collateral and formulating enforceable judgments; and strengthening Sharia governance to ensure uniform standards of evidence, oversight, and transparency. This synergy aims to reconcile the principle of simple, fast, and low-cost justice with transaction certainty, thereby protecting both access to justice and creditor rights.   Abstrak: Penyelesaian sengketa ekonomi syariah yang melibatkan jaminan tanah tanpa Hak Tanggungan menampilkan ketegangan antara efisiensi prosedur dan kepastian perlindungan bagi kreditur. Kajian ini menelusuri pola putusan Pengadilan Agama melalui studi kasus Sumenep No. 1/Pdt.G.S/2020/PA.Smp, memadukan telaah normatif atas undang-undang dan regulasi peradilan dengan pembacaan empiris terhadap putusan. Temuan menunjukkan orientasi pro-efisiensi yakni gugatan sederhana diterima, keabsahan perjanjian ditegakkan berdasar Pasal 1320 KUH Perdata, dan akses keadilan bagi nilai sengketa kecil meningkat. Konsekuensinya, posisi kreditur melemah karena agunan non-Hak Tanggungan tidak menghadirkan titel eksekutorial maupun hak preferen. Pemetaan menegaskan kekosongan pengaturan teknis tentang agunan non-HT di ranah ekonomi syariah dan variasi pertimbangan yudisial antarperkara. Kerangka maṣlaḥah mursalah menilai kemanfaatan percepatan proses hanya sahih bila tidak menggerus kepastian eksekusi, sedangkan saddu az-żarī’ah menuntut penutupan celah yang membuka peluang mudarat seperti perilaku oportunistik debitur dan lonjakan biaya pembiayaan. Rekomendasi diarahkan pada harmonisasi UU Hak Tanggungan, UU Peradilan Agama, dan ketentuan gugatan sederhana, penyusunan pedoman teknis nasional bagi hakim terkait verifikasi jaminan non-HT serta amar eksekusi yang operasional, dan penguatan tata kelola syariah agar standar pembuktian, pengawasan, dan transparansi seragam. Sinergi ini diharapkan menyatukan asas sederhana-cepat-biaya ringan dengan kepastian transaksi jaminan, sehingga akses dan hak kreditur sama-sama terlindungi.